Orotracheal fibreoptic intubation for rapid sequence induction of anaesthesia. - Pandit, J; Dravid, R; Iyer, R; Popat, M (2002)
We assessed whether flexible fibreoptic-guided orotracheal intubation could be rapidly and successfully achieved during a simulated rapid sequence induction in 30 anaesthetised and paralysed patients. Rapid sequence induction was simulated by applying practised cricoid pressure. Using a flexible fibreoptic laryngoscope with camera and closed circuit television, an anaesthetist experienced with the technique performed orotracheal endoscopy and intubation with a cuffed 7.0-mm Portex tracheal tube through a VBM Bronchoscope Airway. Fibreoptic intubation was successful at the first attempt in 28 patients (93%); two patients required two attempts. Mean (SD) time from removal of the facemask from the patient's face to the appearance of carbon dioxide in the expired breath after intubation was 111 (46) s (median 100 s; range 54-195 s). There were one or more difficulties in 13 patients (43%). These difficulties were largely avoidable and included problems with fibreoptic equipment, the Bronchoscope Airway, copious secretions, cricoid pressure or railroading of the tracheal tube. Flexible fibreoptic-guided orotracheal intubation may have a place in the management of failed intubation during a rapid sequence induction.